Transition to the quantum hall regime in InAs nanowire cross-junctions - Gooth, Johannes; Borg, Mattias; Schmid, Heinz; Bologna, Nicolas; Rossell, Marta D.; Wirths, Stephan; Moselund, Kirsten; Nielsch, Kornelius; Riel, Heike (Semiconductor Science and Technology, 2019)
We present a low-temperature electrical transport study on four-terminal ballistic InAs nanowire cross-junctions in magnetic fields aligned perpendicular to the cross-plane. Two-terminal longitudinal conductance measurements between opposing contact terminals reveal typical 1D conductance quantization at zero magnetic field. As the magnetic field is applied, the 1D bands evolve into hybrid magneto-electric sub-levels that eventually transform into Landau levels for the widest nanowire devices investigated (width = 100 nm). Hall measurements in a four-terminal configuration on these devices show plateaus in the transverse Hall resistance at high magnetic fields that scale with (ve 2 /h) -1 . e is the elementary charge, h denotes Planck's constant and v is an integer that coincides with the Landau level index determined from the longitudinal conductance measurements. While the 1D conductance quantization in zero magnetic field is fragile against disorder at the NW surface, the plateaus in the Hall resistance at high fields remain robust as expected for a topologically protected Quantum Hall phase.
CRIS-Team Scopus Importer:2022-04-14
Keywords: conductance quantization; InAs; magneto-transport; nanowire; TASE